Sampling and analysis of environmental chemical pollutants a complete guide - Popek, Emma P. (Amsterdam ; Boston : Academic Press, 2003)
An excellent introduction to the real world of environmental work, this title helps both college students and working professionals improve their understanding of the data collection process. It covers all phases of data collection (planning, field sampling, laboratory analysis, and data quality assessment), and is a single source comprehensive reference for the resolution of the most common problems that environmental professionals face daily in their work. Why This Title This title is written in a clear and logical manner that is accessible to environmental professionals of all disciplines. It contains hundreds of practical tips on planning, sampling, and interactions with analytical laboratories. Having this text as a desk reference will greatly improve skills in planning and sampling, and elevate understanding of chemical data to a new level. This topic is of importance to a wide range of environmental professionals from a variety of disciplines (see audience). Written by a practicing professional for practicing professionals, this handbook provides everything an environmental professional needs to know to competently collect environmental chemical data.
The Sample and the Error. -- 1.1 The Concept of Relevant and Valid Data. -- 1.2 Importance of a Stepwise Approach. -- 1.3 Seven Steps of the Sample's Life. -- 1.4 Total Error and Its Sources. -- 1.5 Total Error and Data Usability. -- Bird's Eye View of Project Planning. -- 2.1 What are Data Quality Objectives? -- 2.2 De.nitive, Screening, and Effective Data. -- 2.3 Regulatory Overview and Action Levels. -- 2.4 How to Navigate the Analytical Method Maze. -- 2.5 Sampling Strategies. -- 2.6 Field Quality Control and Quality Assurance Samples. -- 2.7 Cost Estimate. -- 2.8 Planning Documents. -- 2.9 Analytical Method and Laboratory Selection. -- 2.10 Preparedness and Coordination. -- Practical Approach to Sampling. -- 3.1 Seven Steps of the Sampling Process. -- 3.2 Sample Custody and Tracking. -- 3.3 Sample Preservation Techniques. -- 3.4 Sample Packaging and Shipment. -- 3.5 Soil Sampling Designs. -- 3.6 Water Sampling. -- 3.7 Surface Sampling with Wipes. -- 3.8 Equipment Decontamination. -- 3.9 Field Measurements. -- 3.10 Field Records. -- Understanding the Analytical Laboratory. -- 4.1 Requirements for Laboratory Operation. -- 4.2 Laboratory Organization. -- 4.3 The Seven Steps of Laboratory Process. -- 4.4 Analytical Techniques and Their Applications. -- 4.5 Compound Quantitation. -- 4.6 Laboratory Quality Assurance. -- Data QualityAssessment. -- 5.1 Data Evaluation. -- 5.2 The Seven Steps of Data Evaluation. -- 5.3 The Seven Steps of the Data Quality Assessment.
Includes bibliographical references (p. 343-346) and index.
Keywords: Pollutants -- Analysis; Environmental sampling; Electronic books